2016
DOI: 10.1037/xhp0000198
|View full text |Cite
|
Sign up to set email alerts
|

Influence of musical groove on postural sway.

Abstract: Timescales of postural fluctuation reflect underlying neuromuscular processes in balance control that are influenced by sensory information and the performance of concurrent cognitive and motor tasks. An open question is how postural fluctuations entrain to complex environmental rhythms, such as in music, which also vary on multiple timescales. Musical groove describes the property of music that encourages auditory-motor synchronization and is used to study voluntary motor entrainment to rhythmic sounds. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
71
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(83 citation statements)
references
References 52 publications
(90 reference statements)
8
71
1
Order By: Relevance
“…The multi-scale correspondences between music and CoP sway found by Ross et al (2016) shed light on the complex mechanisms that underlie human posture control and its sensorimotor aspects. It has been shown that the human posture control system is not based on one single physical principle.…”
Section: Music-induced Movementmentioning
confidence: 96%
See 2 more Smart Citations
“…The multi-scale correspondences between music and CoP sway found by Ross et al (2016) shed light on the complex mechanisms that underlie human posture control and its sensorimotor aspects. It has been shown that the human posture control system is not based on one single physical principle.…”
Section: Music-induced Movementmentioning
confidence: 96%
“…Previously, Ross et al (2016) explored the influence of musical groove on balance control mechanisms during standing. This was done by correlating events in the recorded center of pressure (CoP) time series with events in the music stimuli of varying groove content.…”
Section: Music-induced Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…A tight relationship between movement and auditory rhythm perception is evident in human motor system response and motor involvement during music listening and rhythm tasks (Iversen & Balasubramaniam, 2016;Janata, Tomic, & Haberman, 2012;Repp, 2005a;Repp, 2005b;Ross, Warlaumont, Abney, Rigoli, & Balasubramaniam, 2016), and can be observed in neural response to music early in infant development (Kuhl, Ramirez, Bosseler, Lin, & Imada, 2014). How we move to music has by itself become a systematic subfield of inquiry (Ross et al, 2016) that often focuses on body synchronization with music.…”
Section: Introductionmentioning
confidence: 99%
“…How we move to music has by itself become a systematic subfield of inquiry (Ross et al, 2016) that often focuses on body synchronization with music. Some have suggested that the link between auditory and motor involvement in music could be similar to that found in language (Patel, Iversen, & Rosenberg, 2006).…”
Section: Introductionmentioning
confidence: 99%